PENGARUH PRODUCT INNOVATION DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE OPPO - Elprida Silalahi ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
This study is entitled The Effect of Product Innovation and Brand Image on the Oppo Smartphone Purchasing Decision on Consumer Stores in Jaya Mobile, Skip City Bengkulu Branch. The formulation of the problem in this research is whether Product Innovation and Brand Image have a significant effect on the Oppo Smartphone Purchase Decision on the Consumer of Jaya Toko's Skip Surabaya Bengkulu Branch. The purpose of this study was to determine the effect of Product Innovation and Brand Image significantly influence the Oppo Smartphone Purchase Decision on Consumer Stores Jaya Skip Surabaya City Branch. This research was conducted on Oppo Smartphone Consumers at Toko Jaya Ponsel Simpang Skip Branch in Bengkulu City. While the time of the study for 14 days namely on January 26 to February 8, 2020. The population of this study is the Oppo smartphone consumers Toko Jaya Ponsel Skip Bengkulu City Branch, while the sample of this study is the oppo smartphone consumers Toko Jaya Ponsel Skip Bengkulu City Branch totaling 100 respondents and use quantitative methods. With the research test data analysis technique, the results of the study can be concluded that the respondents' perceptions about Product Innovation (X1) and Brand Image (X2) affect the Purchasing Decision (Y) with the results of multiple linear regression obtained the following equation: Y = 4.891 + 0.633 (X_1 ) + 0.507 (X_2). And the coefficient of determination of R2 = 0.837 or 83.7% through hypothesis testing together (simultaneous) and individually (partial) in this study using the f test and t test, Product Innovation (X1) and Brand Image (X2) = 0.000, it means that the value of fsig <0.05 together and a significant influence. Keywords: Product Innovation, Brand Image and Decision